Drug therapy in nursing - Aschenbrenner, Diane S. (Lippincott Williams & Wilkins, 2002)
Johns Hopkins Univ., Baltimore, MD. Textbook presents a nursing-focused framework to support the teaching and learning of nursing pharmacology. Features concept maps, physiology figures, memory chips, community-based concerns, critical thinking scenarios, drug summary tables, and drug interaction tables.